The clinical course of asymptomatic esophageal candidiasis incidentally diagnosed in general health inspection. (December 2015) - Lee, Sang Pyo; Sung, In-Kyung; Kim, Jeong Hwan; Lee, Sun-Young; Park, Hyung Seok; Shim, Chan Sup
Abstract Objective. Esophageal candidiasis mostly occurs in the immunocompromised host. However, it may also affect healthy people and is frequently asymptomatic. The clinical significance of asymptomatic esophageal candidiasis (AEC) is still unclear. The aims of the study were to investigate the prevalence of AEC during health inspection and to identify its predisposing factors and clinical significance. Materials and methods. A total of 49, 497 subjects who underwent a health inspection that included upper endoscopy were enrolled. We retrospectively reviewed the subject's self-reporting questionnaires, medical records and endoscopic findings. We considered "long-term" follow-up to be >6 months with at least one more follow-up endoscopy. Results. One hundred and seventy (0.4%) subjects were endoscopically diagnosed as esophageal candidiasis and 141 subjects were AEC. Multivariate analysis revealed that old age (≥60 years) was an independent risk factor for AEC (OR, 1.862, p = 0.005). The number of subjects with long-term follow-up was 79 (195.3 person-years). Among these, AEC of 64 subjects (81.0%) had disappeared on the follow-up endoscopy and was not recurrent. The other 15 subjects had AEC diagnosed more than once on the follow-up endoscopy, and 5 of them were spontaneously healed during the follow-up period. The remaining 10 subjects whose candidiasis was sustained up to the last endoscopy did not complain of symptoms during the follow-up period, and their endoscopic findings did not worsen. Conclusions. AEC is rare and old age is the only risk factor. AEC does not require medical care because it is a self-limited disease.